Possible impact of disease and reproductive wastage on the productivity of tropical small ruminants: An overview - Mukasa-Mugerwa, E. (International Livestock Research Institute, 1996)
Small ruminants contribute significantly to meat (and sometimes milk) production in Africa and hence in meeting the current shortfall created by the fast rising human population. Flock productivity may, however, be affected by a wide range of disease problems and reproductive wastage. The impact of disease may be through mortalities and abortions or through morbidity and such subclinical effects like weight loss or reduced gains, reduced carcass weight and quality and the cost of time and money involved in controlling or overcoming the effects of disease. Thus, a top priority in operating successful small ruminant enterprises must be adequate attention to health problems and the causes or reproductive wastage. Losses due to mortality often have severe and easily quantifiable economic impact but losses in production due to morbidity are commonly underestimated because they are difficult to estimate. This paper provides a background against which specific effects of the role of health problems and reproductive wastage on production can be discussed.